1998
DOI: 10.1046/j.1471-4159.1998.70020452.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Systemic Inflammatory Response and Cytokines on the Transcription of the Genes Encoding Cyclooxygenase Enzymes (COX‐1 and COX‐2) in the Rat Brain

Abstract: Abstract:The aim of this study was to investigate the influence of the acute-phase response and the promflammatory cytokines on the transcription of the genes encoding the limiting enzymes for the production of prostaglandins, cyclooxygenase (COX)-1 and COX-2, in the rat brain. The bacterial endotoxin lipopolysaccharide (intravenous and intraperitoneal) and turpentine (intramuscular) were used as different models of inflammation in adult male rats. Animals were also killed at various times after intravenous ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
1
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(150 citation statements)
references
References 76 publications
9
136
1
4
Order By: Relevance
“…Prominent induction of COX-2 mRNA has been noted specifically within the parenchyma of the hypothalamic paraventricular nucleus (15). In accord with the effects we observed on food intake after LPS administration, COX-2 has also been demonstrated to be the COX isoform essential for generation of the febrile response after systemic inflammation (20).…”
Section: Discussionsupporting
confidence: 82%
“…Prominent induction of COX-2 mRNA has been noted specifically within the parenchyma of the hypothalamic paraventricular nucleus (15). In accord with the effects we observed on food intake after LPS administration, COX-2 has also been demonstrated to be the COX isoform essential for generation of the febrile response after systemic inflammation (20).…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we found low brain uptake of [ 11 C]rofecoxib (SUV: 0.26±0.09), supposedly reflecting the low expression levels of COX-2 in the brain. In situ hybridization studies have demonstrated that constitutively expressed COX-2 mRNA is not homogeneously distributed in the brain but predominantly located in cortical areas and hippocampus [17,18]. In this study, we showed that the [ 11 C]rofecoxib distribution corresponds with the known distribution of COX-2 mRNA.…”
Section: Discussionsupporting
confidence: 52%
“…This NS398-induced change in distribution pattern was accompanied by a significant reduction (P b.01) in [ 11 C]rofecoxib accumulation in cingulate/frontopolar cortex (−41%, P=.01), whereas the reduction in hippocampus almost reached significance (−33%, P=.06). These brain regions are known to express significant basal levels of COX-2 in healthy animals [17,18]. Prolongation of the interval between NS398 administration and tracer injection from 5 to 60 min did not result in a significantly greater blockade of tracer binding, indicating that NS398 binding to COX-2 is virtually complete within 5 min.…”
Section: [ 11 C]rofecoxib Distribution In Healthy Rat Brainmentioning
confidence: 90%
See 1 more Smart Citation
“…COX-2, on the other hand, is constitutively expressed at low levels in neurons of the cortex, hippocampus, and amygdala, but not in the cells of the cerebral vasculature (34). COX-2 is strongly induced in brain vasculature, however, by LPS and IL-1␤ (12,22,34). LPS or cytokines (31) transiently enhance COX-2 mRNA and protein levels via activation of nuclear factor-B (2, 23).…”
mentioning
confidence: 99%